Organic sol-gel method in the synthesis and characterization of zinc oxide nanoparticles - Lee, K. (Science Publications, 2014)
Nanosized Zinc Oxide (ZnO) was synthesized using sol-gel method. The nanomaterials with structure were annealed at different temperatures ranging from 500 to 700Â°C which were chosen based on the Thermogravimetric (TGA) Analysis. The structure and morphology were characterized by Powder XRay Diffraction (PXRD) and Transmission Electron Microscope (TEM), respectively. The PXRD shows the increasing tendency in crystallite size when the annealing temperature increases and the hexagonal structure of ZnO. TEM further revealed the same tendency which the Zn NPs size increased with the annealing temperature. Â© 2014 Science Publication.